In search of a model to explain digital divide in information technology organizations - Mohamed, Norshidah; Hussein, Ramlah; Ahlan, Abdul Rahman (2009)
Innovations in information technology have enabled organizations shape new business rules and create competitive advantage. Information technology provides opportunities for the creation of wealth from knowledge-based economic activities which contribute to the GDP. Successful creation of knowledge-based society primarily relies on narrowing the digital divide.